Spaces of power in Berber North Africa under Carthaginian and Roman rule: the case of Cirta (Constantine, Algeria) - Kormikiari, Maria Cristina Nicolau (Romanitas - Revista de Estudos Grecolatinos, 2014)
The present paper addresses the spatial use and the social organization of the surrounding area of the ancient city of Cirta, modern Constantine, in Algeria. Our aim is to systematize a hypothesis that will emerge from archaeological data, and textual and epigraphic evidences, on the occupation of the territory by North-African native tribes, those that area part of the Numidian confederations. In order to achieve that, we will also discuss the relation between these tribes and Carthagianian domains and then their relation to the Roman Empire.